STUDENTS’ ERROR ANALYSIS IN WRITING ESSAY OF ENGLISH LANGUAGE TEACHING - Saputra, Riyadi (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
One of the successful learning English writings is by knowing students' errors in writing an English essay. Since English writing essay becomes a compulsory subject that must be taken by students at college, therefore the English essay has a big contribution. Although writing an English essay does not pay attention much to the proportional explaining and giving instruction in learning, but it still has meaningful contributions for writing skill. It is not for writing essay but also for other writing skills such as writing paragraph, writing scientific paper, and etc. Type of this research was qualitative content analysis through documents of English essays written by students of third semester of Universitas Dharmas Indonesia. Respondents of this research were 14 students. The analysis of all documents reveals that there are 220 total numbers of students’ errors that classified into 12 types of errors made by the students. Spelling is classified as the biggest error committed by 46 times or 20.90%. Then, verb-agreement is a kind of errors that committed by 38 times or 17.27%. Next is error of sentence fragment that committed by 24 times or 10.90%. Relating to research finding, It is recommended that English writing lecturers should much pay attention to divide, discuss, and explain all these errors in order to minimize and make writing essays easy written and conducted by English students.